Antibacterial activity of selected plants used in ethnoveterinary medicine - Mahlo, Salome Mamokone (University of Limpopo (Turfloop Campus), 2006)
Refer to document
Thesis (M.Sc. (Agriculture)) --University of Limpopo, 2006
Keywords: Antibacterial activity; Ethnoveterinary medicine; 636.089; Veterinary medicine -- South Africa; Ethnozoology -- South Africa